Frontier Therapeutics and Vaccine Strategies for SARS-CoV-2 (COVID-19): A Review - Amirhossein SHEIKHSHAHROKH; Reza RANJBAR; Elnaz SAEIDI; Farhad SAFARPOOR DEHKORDI; Mohammad HEIAT; Payam GHASEMI-DEHKORDI; Hamed GOODARZI (Tehran University of Medical Sciences, 2020)
COVID-19 is considered as the third human coronavirus and has a high potential for transmission. Fast public health interventions through antibodies, anti-virals or novel vaccine strategies to control the virus and disease transmission have been extremely followed. SARS-CoV-2 shares about 79% genomic similarity with SARS-CoV and approximately 50% with MERS-CoV. Based on these similarities, prior knowledge in treating SARS-CoV and MERS-CoV can be used as the basis of majority of the alternatives for controlling SARS-CoV-2. Immunotherapy is an effective strategy for clinical treatment of infectious diseases such as SARS-CoV-2. Passive antibody therapy, which decreases the virus replication and disease severity, is assessed as an effective therapeutic approach to control SARS-CoV-2 epidemics. The close similarity between SARS-CoV-2 genome with the SARS-CoV genome caused both coronaviruses to bind to the same angiotensin-converting enzyme 2 (ACE2) receptors that found in the human lung. There are several strategies to develop SARS-CoV-2 vaccines, which the majority of them are based on those developed previously for SARS-CoV. The interaction between the spike (S) protein of SARS-CoV-2 and ACE2 on the host cell surface leads to the initiation of SARS-CoV-2 infection. S protein, which is the main inducer of neutralizing antibodies, has been targeted by most of these strategies. Vaccines that induce an immune response against the S protein to inhibit its binding with the host ACE2 receptor, can be considered as effective vaccines against SARS-CoV-2. Here, we aimed to review frontier therapeutics and vaccination strategies for SARS-CoV-2 (COVID-19).